Propostas para melhoria da gestão de utilities na Prefeitura de São Paulo - Dantas, Maurício Geraldo da Silva (2012)
The Planning, Budget and Management Secretariat of São Paulo City (Secretaria de Planejamento, Orçamento e Gestão da Cidade de São Paulo), SEMPLA, through the Coordinating body of Economic Studies (Coordenadoria de Estudos Econômicos), CDEC, requested a study aimed at compiling information on expenditures and consumption in all PMSP services related to water supply, electricity and telephony system, known as utilities, as well as the presentation of a set of recommendations for rationalizing expenditures and improving the management model. The received data were analyzed separately for each of the utility services. Water and electricity have been analyzed the historical record of commitment values and the records of consumption, not applicable in telephony service because of the absence of such information. Simultaneously with the diagnosis, were also studied processes for payments of bills, mostly to identify the form to approve the services. Meetings were held with the main executives of these processes for the formulation of explanatory models of existing problems, with the aid of tool management analysis and research with the managers responsible for units of consumption. From the compilation of these elements, a specific diagnosis was established for each utility and a more comprehensive understanding of structural and functional limitations of the current management group – Concessions Group (Grupo das Concessionárias). As a result, a separate list of recommendations and Project mandates, indicating the necessary steps to improve the management process, reducing consumption and achieving better demonstration of the effectiveness of expenditure.